Characterization of YVO4:Eu3+ scintillator as detector for Fiber Optic Dosimetry. (November 2017) - Martínez, N.; Rucci, A.; Marcazzó, J.; Molina, P.; Santiago, M.; Cravero, W.
Abstract: Fiberoptic dosimetry (FOD) is an experimental technique suitable for in-vivo, real time dosimetry in radiotherapy treatments. In a previous work it was found that YVO4 :Eu is a scintillator suitable to be employed as scintillator for FOD in pulsed MV photon beams. YVO4 :Eu-based FOD probes have shown several positive characteristics: temperature independence; no previous irradiation needed; good spatial resolution. In this paper others dosimetric characteristics have been investigated for the first time. Suitability for real time dosimetry has been determined by simultaneous measurement with a ionization chamber; off axis profile have been obtained in order to assess spatial resolution of the FOD system when used in fields having a size of 3 × 3cm 2 and 1 × 1cm 2 ; angular dependence has been studied for probes with cylindrical and quasi-spherical geometry showing the influence of the detector shape on it isotropy. Additionally, PDD curves resulting from Monte Carlo simulations have been successfully compared to experimental curves. Highlights: YVO4 :Eu-based dosimetric probes are suitable for real time dosimetry. YVO4 :Eu response shows repeatability and independence with accumulated dose within therapeutic range. Isotropic response is observed if the detector is spherically shaped.